Camp X-ray / [videorecording (DVD)] - Sattler, Peter (Director); Stewart, Kristen, 1990-; Muʻādī, Paymān, 1972-; Garrison, Lane, 1980- (IFC Films, 2015)
A young soldier is stationed as a guard at Guantanamo Bay where she strikes up an unusual and potentially dangerous friendship with a detainee who has been imprisoned for eight years.